Factors affecting the intention of Iranian rural women to use medicinal herbs - Heshmatollah Saadi; Somayeh Jafari; Saeid Karimi (BMC, 2023)
Abstract Background This study aimed to identify factors affecting the behavioral intention of Iranian rural women to use medicinal herbs. The research model was developed by integrating "dissatisfaction with modern medicine" into the "theory of planned behavior". Methods Data were collected through questionnaire from a sample of 260 Iranian rural women, which were randomly selected. The validity and reliability of the scale were confirmed using expert opinions and Cronbach's alpha method, respectively. Results Based on the results of structural equation modeling, attitude (β = 0.44; p < 0.01), subjective norms (β = 0.27; p < 0.01) and dissatisfaction with modern medicine (β = 0.11; p < 0.05) had significant positive effects on rural women's intention to use medicinal herbs. In addition, subjective norms indirectly affected rural women's intention to use medicinal herbs through attitude (β = 0.23; p < 0.01). Conclusions Subjective norms was a key factor in determining the intention of Iranian rural women to use medicinal herbs, followed by attitude and dissatisfaction with modern medicine. Therefore, this study could contribute to our understanding on how the intention of Iranian rural women to use medicinal herbs was influenced by different factors.